Belles on their toes [videorecording (DVD)]. - Loy, Myrna, 1905-1993; Hunter, Jeffrey; Crain, Jeanne (20th Century Fox, 1952)
In this sequel to Cheaper By The Dozen, Ann Gilbreth is forced to take over as the primary breadwinner after the death of her husband, but she soon discovers that not every company who hired her and her husband is eager to work with her on her own.